An investigation on microfluidic droplet formation, reagent addition and mixing - Sivasamy Jayaprakash (2012)
Significant efforts have been targeted towards developing a droplet-based microfluidic system and understanding the droplet formation process and the physics behind it and yet the underlying physics of the droplet formation in terms of evolution of pressures in both the continuous phase and dispersed phase has received less attention over the years and is not understood clearly. A numerical investigation on the mechanism of droplet formation in a microfluidic T-junction has been conducted and validated against the experimental flow visualisation. From the computational results it is shown that the pressure profile of the dispersed phase and the continuous phase in the squeezing regime changes as the droplet break-up process proceeds. New insights on the droplet break-up process such as the minimum pressure difference between the continuous phase and the dispersed phase happens at the last moment of the the droplet break-up and not during the second and third stage of the droplet formation mechanism in the squeezing regime have been identified. As a next step in the analysis, reagent addition to microfluidic droplets is a fundamental operation in high-throughput screenings. Adding precise amount of reagents to droplets poses difficulties and many of the available designs use complicated structures and fabrication methods. A design that reliably adds reagents into droplets by exploiting the physics of fluid flow at an expanded section right after the T-junction which enhances merging of a stream with a droplet, eliminates the drawbacks such as extra droplet formation and long mixing time is demonstrated. Experimental results show that the expanded section minimizes the tendency to form extra droplets; the reactants are in axial arrangement inside the droplets which leads to faster mixing; reliable addition of reagent to the droplets happens for the combination of flow rates in a broad range of both substrate and reagent streams. To understand the physics behind the reliable operation of reagent addition, a numerical investigation using VOF model has been conducted. The flow field and the pressure measurements show that when an expanded section is used, the dynamics of droplet formation mechanism undergoes a significant change and is dominated by the combination of both shear stress and pressure buildup-based droplet breakup from a pure pressured buildup-based droplet breakup in the squeezing regime; and the expanded section plays the role in creating low Laplace pressure jump across the interface of the droplet forming from the T-junction which reduces the probability of forming extra droplet in the merging process.